PEMBANGUNAN GEOPORTAL JARINGAN INFORMASI GEOSPASIAL DALAM MENUNJANG KETERSEDIAAN DATA DAN PENINGKATAN KINERJA SDM KABUPATEN GRESIK - Fauzan Roziqin; Fatimah Zahro; Adipandang Yudono (REKSABUMI, 2023)
In the management of the regional geospatial information network, evaluation needs to be carried out as a continuous improvement effort. The assessment focuses on both internal and external aspects in the process of geospatial information management. The purpose of this study is to determine the readiness of the development of the geoportal, the availability of data and human resources in Gresik District, as well as to identify the strengths and weaknesses. The method used in this research is descriptive analytic method, which identifies, evaluates, and assesses each instrument through data scanning and interviews. The results of this study show that the Gresik District Geospatial and Geodetic Network Node has achieved an "Operational" status, compared to before when it did not exist. Gresik District is now joined by 38 other districts/cities with an "Operational" status. The evaluation value falls into class B, which means the maximum development time is 12 months. In addition to the availability of the geoportal, Gresik District also has a data forum, but there is no Spatial Data Forum, so in the future the need for this forum becomes very important to support the improvement of the network node in Gresik District.